A bibliometric analysis of evolving trends in climate change and accounting research - Doddy Setiawan; Isna Putri Rahmawati; Arif Santoso (Cogent Business & Management, 2023)
Although studies on climate change and accounting have garnered paramount interest in last decade, there is a void in the literature in terms of a summary overview of climate change and accounting. This study aims to provide a state-of-the-art summary of the literature on climate change and accounting. For this, it uses the PRISMA protocol, VOSViewer, and R. The analysis is based on big data from Scopus for the period between 2013 and 2023. Similarly, co-occurrence and co-authorship analyses are also performed. The results show a significant increase in related research during the last decade, which reached its peak in 2022. This increase is attributed to increased publishing opportunities and intensive efforts, particularly in countries such as China and United States. Additionally, robust organizational support, such as universities, funding sponsors, and author productivity, are found to significantly contribute to this growth. Key events, such as the Paris Agreement, Sustainable Development Goals (SDGs), and accounting standards also play a pivotal role in driving this growth. This study shows the transformation of the accounting literature in addressing climate change, leading to the emergence of new disciplines, including Environmental Management Accounting (EMA) and carbon accounting. In conclusion, this study provides a comprehensive synthesis of the fragmented literature and suggests potential avenues for future review.
Keywords: 650; accounting; bibliometric; climate change; environmental management accounting; sustainability